Low energy availability, carbohydrate intake, and relative energy deficiency in sport: the low triiodothyronine hypothesis - Hackney, A. C.; Moore, S. R.; Smith-Ryan, A. (International Journal of Sports Physiology and Performance, 2026)
Background: Recent research findings suggest that a daily diet containing low carbohydrate (LCHO) consumption coupled with low energy availability (LEA, specifically what is termed problematic LEA [P-LEA]) exacerbates the risk of developing relative energy deficiency in sport (REDs). Regrettably, research evidence also indicates that dietary carbohydrates are likely underconsumed by many athletes in their daily diets. How these factors, P-LEA and LCHO intake, interact to precipitate the amplification of REDs risk is currently not entirely clear and is the source of much speculation. Purpose: As such, we present herein a hypothetical model of how LCHO dietary intake and P-LEA exposure can interact to create an amplification of the endocrine disruptions associated with REDs, specifically via the development of a low triiodothyronine (T3) state, clinically referred to as low T3 syndrome. The hypothesis presented postulates that P-LEA + LCHO interact to promote reductions in T3 levels in part by inducing a greater cortisol response (at rest or exercise), which in turn inhibits the endocrine function involving the production of T3, as well as the conversion of thyroxine to T3. The resultant low T3 state in turn amplifies the negative hormonal consequences associated with REDs (eg, reduced reproductive, anabolic, and metabolic hormone levels). Conclusions: Practically speaking, athletes and their coaches must recognize the importance of carbohydrates in the diet, specifically the amounts and the timing of their consumption; strive to avoid P-LEA exposure; and monitor for REDs indicators (eg, T3). Researchers are encouraged to pursue investigations to challenge and evaluate our proposed hypothesis concerning how low T3 is the critical factor in the negative hormonal consequences of REDs and the role cortisol plays in these outcomes.